Book Reviews - Redactie KITLV (NWIG, 2008)
Frederick H. Smith; Caribbean Rum: A Social and Economic History (Franklin W. Knight)

Stephan Palmié; Wizards and Scientists: Explorations in Afro-Cuban Modernity and Tradition (Julie Skurski)

Miguel A. De la Torre; The Quest for the Cuban Christ: A Historical Search (Fernando Picó)

L. Antonio Curet, Shannon Lee Dawdy & Gabino La Rosa Corzo (eds.); Dialogues in Cuban Archaeology (David M. Pendergast)

Jill Lane; Blackface Cuba, 1840-1895 (Arthur Knight)

Hal Klepak; Cuba’s Military 1990-2005: Revolutionary Soldiers during Counter-Revolutionary Times (Antoni Kapcia)

Lydia Chávez (ed.); Capitalism, God, and a Good Cigar: Cuba Enters the Twenty-First Century (Ann Marie Stock)

Diane Accaria-Zavala & Rodolfo Popelnik (eds.); Prospero’s Isles: The Presence of the Caribbean in the American Imaginary (Sean X. Goudie)

Alexandra Isfahani-Hammond (ed.); The Masters and the Slaves: Plantation Relations and Mestizaje in American Imaginaries (Danielle D. Smith)

David J. Weber; Bárbaros: Spaniards and Their Savages in the Age of Enlightenment (Neil L. Whitehead)

Larry Gragg; Englishmen Transplanted: The English Colonization of Barbados, 1627-1660 (Richard S. Dunn)

Jon F. Sensbach; Rebecca’s Revival: Creating Black Christianity in the Atlantic World (Aaron Spencer Fogleman)

Jennifer L. Morgan; Laboring Women: Reproduction and Gender in New World Slavery (Verene A. Shepherd)

Jorge Luis Chinea; Race and Labor in the Hispanic Caribbean: The West Indian Immigrant Worker Experience in Nineteenth-Century Puerto Rico, 1800-1850 (Juan José Baldrich)

Constance R. Sutton (ed.); Revisiting Caribbean Labour: Essays in Honour of O. Nigel Bolland (Mary Chamberlain)

Gert Oostindie; Paradise Overseas: The Dutch Caribbean: Colonialism and its Transatlantic Legacies (Bridget Brereton)

Allan Pred; The Past Is Not Dead: Facts, Fictions, and Enduring Racial Stereotypes (Karen Fog Olwig)

James C. Riley; Poverty and Life Expectancy: The Jamaica Paradox (Cruz María Nazario)

Lucia M. Suárez; The Tears of Hispaniola: Haitian and Dominican Diaspora Memory (J. Michael Dash)

Mary Chamberlain; Family Love in the Diaspora: Migration and the Anglo-Caribbean Experience (Kevin Birth)

Joseph Palacio (ed.); The Garifuna: A Nation Across Borders (Grant Jewell Rich)

Elizabeth M. DeLoughery, Renée K. Goss on & George B. Handley (eds.); Caribbean Literature and the Environment: Between Nature and Culture (Bonham C. Richardson)

Mary Gallagher (ed.); Ici-Là: Place and Displacement in Caribbean Writing in French (Christina Kullberg)

David V. Moskowitz; Caribbean Popular Music: An Encyclopedia of Reggae, Mento, Ska, Rock Steady, and Dancehall (Kenneth Bilby)

John H. McWhorter; Defining Creole (Bettina M. Migge)

Ellen M. Schnepel; In Search of a National Identity: Creole and Politics in Guadeloupe (Paul B. Garrett)